2005
DOI: 10.1007/s00248-004-0056-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Iodide-Oxidizing Bacteria from Iodide-Rich Natural Gas Brines and Seawaters

Abstract: Iodide-oxidizing bacteria (IOB), which oxidize iodide (I-) to molecular iodine (I2), were isolated from iodide-rich (63 microM to 1.2 mM) natural gas brine waters collected from several locations. Agar media containing iodide and starch were prepared, and brine waters were spread directly on the media. The IOB, which appeared as purple colonies, were obtained from 28 of the 44 brine waters. The population sizes of IOB in the brines were 10(2) to 10(5) colony-forming units (CFU) mL(-1). However, IOB were not de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
124
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 38 publications
1
124
0
1
Order By: Relevance
“…4, 5) could indicate similar production and sink processes at depth. Bacterial formation of CH 2 I 2 (Fuse et al, 2003;Amachi et al, 2005) in the upper thermocline could also be an additional source for this compound. Alternatively, CH 2 I 2 may not degrade as quickly as CHBr 3 and CH 3 I in greater depths, which would lead to its accumulation below the mixed layer.…”
Section: Ch 3 I and Ch 2 Imentioning
confidence: 99%
“…4, 5) could indicate similar production and sink processes at depth. Bacterial formation of CH 2 I 2 (Fuse et al, 2003;Amachi et al, 2005) in the upper thermocline could also be an additional source for this compound. Alternatively, CH 2 I 2 may not degrade as quickly as CHBr 3 and CH 3 I in greater depths, which would lead to its accumulation below the mixed layer.…”
Section: Ch 3 I and Ch 2 Imentioning
confidence: 99%
“…A review of the literature on this subject reveals only one reference to a chloroperoxidase in the fungus Caldariomyces fumago that can oxidise iodide to iodate (Thomas & Hager 1968). Iodoperoxidases are also present in marine bacteria (Gozlan & Margalith 1973, 1974, Amachi et al 2005, though none of these studies found oxidation through to iodate. Another possibility would be that iodide had been incorporated into the phytoplankton cells, or lost as I 2 .…”
Section: Iodide Oxidation To Iodate By Diatomsmentioning
confidence: 99%
“…However, "P. iodooxidans" has not been deposited in any culture collections and is no longer available. Recently, Fuse et al 33) and Amachi et al 8) individually isolated iodide-oxidizing bacteria from marine environmental samples. Phylogenetic analyses showed that iodideoxidizing bacteria could be divided into two groups within the α-subclass of Proteobacteria.…”
Section: Oxidation Of Iodidementioning
confidence: 99%